2013
DOI: 10.1002/etc.2289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of critical body residue data for acute narcosis in aquatic organisms

Abstract: The Environmental Residue Effects Database was evaluated to identify critical body residues of organic chemicals causing acute baseline neutral narcosis in aquatic organisms. Over 15 000 records for >400 chemicals were evaluated. Mean molar critical body residues in the final data set of 161 records for 29 chemicals were within published ranges but varied within and among chemicals and species (~3 orders of magnitude), and lipid normalization did not consistently decrease variability. All 29 chemicals can act … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 73 publications
6
37
0
Order By: Relevance
“…This value corresponds to 60 mmol kg −1 lw and is in the range of CBRs for acute baseline neutral narcosis in small aquatic organisms, assuming ∼5% lipid content. 26,42 This value is broadly consistent with the Redman et al 4 analysis employing the Target Lipid Model. In the latter study, CBRs for the example cVMS substances were estimated for daphnia (D. magna) of 115 mmol kg −1 lw and for C. tentans of 28 mmol kg −1 lw.…”
Section: ■ Model and Parameterssupporting
confidence: 85%
“…This value corresponds to 60 mmol kg −1 lw and is in the range of CBRs for acute baseline neutral narcosis in small aquatic organisms, assuming ∼5% lipid content. 26,42 This value is broadly consistent with the Redman et al 4 analysis employing the Target Lipid Model. In the latter study, CBRs for the example cVMS substances were estimated for daphnia (D. magna) of 115 mmol kg −1 lw and for C. tentans of 28 mmol kg −1 lw.…”
Section: ■ Model and Parameterssupporting
confidence: 85%
“…The lipid content of 120 hpf unexposed zebrafish was 1.63% ± 0.29% (SD) (w/w, fresh wt), and our CBR LIP50 of 167 mmol/kg lipids was very close to the expected range of 40-160 mmol/kg (Van Wezel and Opperhuizen, 1995), but was higher than the mean CBR LIP50 of 53.9 mmol/kg lipid reported for 29 narcotics in algae, invertebrates and fish (McCarty et al, 2013). Our observation that the CBR fits nicely into the expected interval while the lipid normalized CBR is rather high relative to what is expected, may be due to the fact that lipid corrected CBR values are subject to variation in both lipid content and composition, which may compromise their accuracy (McCarty et al, 2013). For sublethal effects we report EBR LIP50 (swim bladder): 16 mmol/kg lipids and EBR LIP50 (sublethal effects): 13 mmol/kg lipids, which are below the range, as expected.…”
Section: Effect Values Were Within Ranges Expected For Baseline Toxicitysupporting
confidence: 64%
“…Recently, van der Heijden et al (2015) showed that CBR values for seven narcotics tested in three species ranged from 2.1 to 16.1 mmol/kg fresh wt. McCarty et al (2013) reviewed a large set of CBR values and reported a mean CBR of 1.80 mmol/kg fresh wt for 29 narcotics in algae, invertebrates and fish. CBR values for phenanthrene in invertebrates ranged from 0.32 to 8.40 mmol/kg (McCarty et al, 2013).…”
Section: Effect Values Were Within Ranges Expected For Baseline Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the relatively short test duration, we assume negligible biotransformation and fish growth to occur during the test. These wet weight lethal body burdens are consistent with values associated with a baseline toxicity (narcotic) mode of action . Input parameters used in these simulations are presented in Tables , , and .…”
Section: Structure and Applications Of The Modelsupporting
confidence: 70%